2008
DOI: 10.1108/17538350810865578
|View full text |Cite
|
Sign up to set email alerts
|

Workplace physical activity interventions: a systematic review

Abstract: Purpose: This paper reports a synopsis of a recent systematic review of the literature regarding the effectiveness of workplace physical activity interventions, commissioned by the National Institute for Health and Clinical Excellence (NICE), UK (Dugdill et al., 2007). Methods:A search for English-language papers published between 1996-2007 was conducted using 12 relevant databases and associated grey literature. Search protocols and analysis regarding study quality as recommended by NICE were utilised (NICE, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
122
3
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(132 citation statements)
references
References 35 publications
(92 reference statements)
3
122
3
4
Order By: Relevance
“…Previous reviews summarizing the literature promoting PA through active commuting and/or through exercise during breaks from productive work have not separated effects on overall PA from those at work (24,27,(81)(82)(83). In general, these reviews conclude that multi-component interventions containing individualized initiatives in combination with organizational and/ or environmental changes, are more effective in increasing PA than single-component interventions.…”
Section: Personalized Behavioral Interventionsmentioning
confidence: 89%
See 1 more Smart Citation
“…Previous reviews summarizing the literature promoting PA through active commuting and/or through exercise during breaks from productive work have not separated effects on overall PA from those at work (24,27,(81)(82)(83). In general, these reviews conclude that multi-component interventions containing individualized initiatives in combination with organizational and/ or environmental changes, are more effective in increasing PA than single-component interventions.…”
Section: Personalized Behavioral Interventionsmentioning
confidence: 89%
“…Subgroup analyses did indeed show that -for interventions including self-monitoring of PA (often with pedometers) -no effect was found on PA at work, but that these interventions were effective in increasing overall PA (moderate evidence). This is a likely result of the fact that, in many occupational settings, the opportunities to substantially increase especially moderate and vigorous PA will be limited due to constraints set by workstations or work tasks.Previous reviews summarizing the literature promoting PA through active commuting and/or through exercise during breaks from productive work have not separated effects on overall PA from those at work (24,27,(81)(82)(83). In general, these reviews conclude that multi-component interventions containing individualized initiatives in combination with organizational and/ or environmental changes, are more effective in increasing PA than single-component interventions.…”
mentioning
confidence: 89%
“…In the last two decades, attention has been directed to promoting health among employees through workplace intervention, and a particular focus given to physical activity (PA) [4]. Besides being associated with reduced risks for several health threats, promoting PA in the workplace have been found to be effective as a stress-management intervention [1].…”
Section: Physical Activity In Workplace As a Stress-management Strategymentioning
confidence: 99%
“…fitness centers nearby or exercise-facilities within the work place), as only 14% of the employees have access to different types of workplace exercise facilities [5]. Although promoting PA by itself can positively impact the stress load among employees [4], giving more attention to the environment the PA takes place in could enhance the possible benefits of the activity, especially in terms of restoration from stress and mental fatigue. Especially, it has been shown that engaging in PA in natural environments can provide greater benefits in terms of psychological responses and stress reduction as compared to exercising indoors [6,7].…”
Section: Physical Activity In Workplace As a Stress-management Strategymentioning
confidence: 99%
“…Nesse contexto, o ambiente de trabalho tem sido valorizado no cenário dos locais favoráveis para a promoção da saúde, através de programas com ações educativas e intervencionistas (4) . Estudos mais recentes acerca da saúde do trabalhador permeiam não apenas as doenças ocupacionais, a redução dos custos e o aumento da produtividade, mas uma abordagem mais ampliada de saúde, no contexto da adoção de comportamentos saudáveis por meio de incentivo ao aumento dos níveis de atividade física, à melhoria na alimentação e aos demais comportamentos preventivos (5)(6)(7)(8) . No Brasil, milhares de pessoas morrem na faixa etária mais produtiva devido às doenças cardiovasculares (9) e, segundo a Organização Mundial da Saúde (3) , parte dessas mortes poderia ter sido evitada se fatores de risco como tabagismo, consumo abusivo de bebidas alcoólicas, sedentarismo, sobrepeso e obesidade tivessem sido modificados a tempo e doenças como hipertensão, hipercolesterolemia e diabetes, diagnosticadas precocemente e devidamente controladas.…”
Section: Introductionunclassified